A Review: Conversion of Glycerol to Solketal - Ruenkhamchan, Natthanan; Kitima, Patcharapa; Sangsarawatt, Sujinda; Rungrojchaipon, Pesak (Journal of Science Ladkrabang, 2022)
Biodiesel is becoming an important biofuel that gain worldwide attention. It is normally produced through the transesterification of triglyceride with alcohol, yielding glycerol as the by-product. As a drawback, increase in biodiesel production has lead to an increase in availability of glycerol. Therefore, there are many research topics focused on the study of converting glycerol into a more valuable and higher price product. The synthesis of solketal from glycerol is another option to increase the value of glycerol. This article has gathered information related to the synthesis of solketal from glycerol using catalysts such as resin, mesoporous silica, clay minerals, hierarchical zeolite, activated carbon and different experimental conditions from various research, to achieve effective conversion of glycerol and selectivity of solketal.